Istirātījiyyatu “‘Arḍu al-Kitāb” ka Taqyīmi Qirāah al-Kutub aṣ-Shafra’ fī Ta’līmi An-Naḥwiyyah lī Tahqīqi at-Ṭalabah ad-Dauliyah: Strategi “Demonstrasi Kitab” Sebagai Evaluasi Pembacaan Kitab Kuning dalam Pembelajaran Nahwu Guna Mencapai Kompetensi Internasional - Shalihah Shalihah; Umi Machmudah; Ghina Hajidah Manaf; Sumarni Sumarni (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
The "Kitab Demonstration" strategy, used as the final evaluation of the entire learning process at Jam'iyah Ta'miq al-Kutub, is important to study because its process is engaging, offers numerous benefits, and generally increases the students' interest in maintaining the typical characteristic of Islamic boarding school students, which is the ability and habit of reading classical texts or Islamic classical books. The research data is sourced from interviews with participants of the Kitab institution, observations, and documentation. In addition, data is also gathered from internet sites and institutional documents. The data collection instruments include interview documents, observation guidelines, and documentation. The data analysis uses qualitative descriptive techniques to describe and reveal the original facts in the field. This study aims to identify the benefits of the "Kitab Demonstration" and to show how this strategy contributes to promoting the students of the Lubangsa Putri Annuqayah Islamic boarding school, under the Jam'iyah Ta'miq Al-Kutub institution, towards national and international recognition in Kitab reading skills. The research results indicate that the Kitab demonstration provides benefits for the students not only in terms of cognitive skills but also in psychological aspects. Furthermore, the contribution of Lubangsa Putri students in elevating the institution’s name on the international stage has been evident over the past ten years since the implementation of the "Kitab Demonstration." Keywords: International Competence, Islamic Classical Books, Kitab Demonstration, Reading Kitab.